Effectiveness Of Scapular Endurance Training In 10m Air Rifle Shooters - Patil, Gargi Nandkumar; Patil, Poonam (Journal of Neonatal Surgery, 2025)
Background: This air rifle event, 10 meters long, is an ISSF-sanctioned precision shooting sport where shooters fire 4.5 mm (.177 caliber) pellets at a target 10 meters away from a standing position. The event requires extraordinary accuracy, stability, and mental concentration because the 10-ring on the target measures only 0.5 mm in diameter, with elite performance often relying on consistently scoring in this tiny area across 60 shots (for men) or 40 shots (for women), all under strict time limits. Success in this sport hinges on combining technical skills, postural stability, and physical conditioning, which demands that the shooter retains stable body posture for a sustained period while counteracting the unnoticeable movements created due to breathing, heart rate, and muscle fatigue. Scapular endurance training is defined as a training program that strengthens and enhances the endurance of the muscles around the shoulder girdle: trapezius, rhomboids, serratus anterior, and rotator cuff muscles. These muscles are crucial for the stabilization of the scapula, which serves as the base for mounting all upper limb activities and the posture. In 10m air rifle shooting, shooters take position in standing, with the rifle supported by the shoulder and arm, which also requires prolonged isometric contractions to maintain a stable hold. Scapular muscles are vital in preventing shoulder fatigue, minimizing barrel movement, and ensuring a consistent aim, particularly during long competitions where fatigue detrimentally affects performance. The rationale for exploring scapular endurance training here is, of course, due to the unique physical demands of the sport. Unlike dynamic sports, air rifle shooting requires static endurance to resist muscle tremors in maintaining precise alignment. Research indicates that inadequate scapular stability leads to compensatory movements that increase barrel sway, making the shot inaccurate. For instance, studies conducted in other shooting disciplines have shown that scapular muscle endurance can be beneficial for shooting performance by increasing upper body stability. However, scientific evidence for this in 10m air rifle shooters is less extensive, hence the interest in assessing whether targeted scapular training may correlate with improved scores or lesser performance variability. Some of the key factors that may determine the success of the training include the level of skill of the shooter (novice or elite), intensity of training, and the extent to which scapular exercises are integrated with other conditioning, such as core stability or balance training. Elite shooters with already superior postural control compared to novices may benefit in a different way, with novices seeing more substantial gains through improvement in basic strength. Also, due to the sheer repetitiveness of holding a 4-5 kg rifle over long durations, it would suggest that endurance as opposed to sheer strength would be the requirement, and thus scapular fatigue resistance may be implicated as performance-determining. Indeed, this subject is important, as it may well provide an edge in competition within a sport where the margins are ever slight. Whether or not training for endurance of the scapula has an effect on shooting performance may also be of interest to coaching personnel who would be better able to guide their shooting athletes into maintaining levels of performance under pressure; however, there is still a number of unexplored areas in the literature, notably standardized protocols for scapular training and long-term effects on shooting metrics such as shot grouping or score variance. Researching this area would also help build the practical side of training with scientific easement and benefit both athlete and coach within the precision sports field. Methods: This randomized clinical trial will assess the impact of an intervention on scapular endurance training in 10 m air rifle shooters. Thirty participants with 10 m air rifle shooters, will be selected via random sampling. Inclusion criteria include the participants aged 18 to 35 years, active 10 m air rifle shooters with at least 2 years of competitive experience, physically healthy and engaging in regular training with 3 times per week . Exclusions include history of shoulder or back injuries in past 6 months, use of medications that affect muscle strength. The outcomes are closed kinetic chain upper extremity stability test, upper quarter Y balance test, prone bridge test, side bridging endurance test, scapular muscle endurance test Participants will undergo a six-week intervention, with data analyzed post-assessment. Ethical approval and informed consent will be obtained. Result: Based on the statistical analysis, the effectiveness of scapular endurance training on accuracy in 10 m air rifle shooters shows highly significant. (p<0.0001). Conclusion: The scapular endurance training proved to be an extremely useful tool for the 10m air rifle shooters, improving scapular stability and endurance and balance. This indicates that such exercises should be incorporated into training regimens; these improvements could serve to enhance performance and perhaps even reduce injury risks. In the future, such developments should be correlated against competition performances to assess their validity further.